From coalitions to social movements: Lessons from civic food coalition formation in Australia - Freeman, Camille; Smith, Kiah (The International Journal of Sociology of Agriculture and Food, 2024)
Despite the abundant literature on the need for grassroots food system reform, the process for achieving such reform is less understood from the perspective of multi-scalar coalition building. Using semi-structured interviews with civic food coalition leaders in Australia, our paper examines the strengths and struggles associated with collectivising, collaborating, and planning that civic food coalitions experience as they aim to drive wider transformations in food systems. Findings indicate a need to pay heightened attention during the early stages of coalition formation, as this is when coalitions form a sustainable structure as they begin to scale up. In addition to gaining a better understanding of these internal dynamics, we argue that civic food coalitions can be one pathway to transform the food system, as they serve as an important catalyst to bring food-related issues (such as social and environmental justice) to the forefront in building alliances and collective action across communities.